THE EFFECT OF HIGH PERFORMANCE WORK SYSTEM ON JOB SATISFACTION EMPLOYEE IN CLASS I DETENTION CENTER LABUHAN DELI - Simbolon, Novelin Nurmala; Kusmiyanti, Kusmiyanti (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research aims to measure the influence of the high-performance work system on employee job satisfaction at the Labuhan Deli Class I Detention Center. This research was conducted using a quantitative approach, emphasizing numerical data analysis using statistical methods. The research sample was 115 respondents. The data analysis technique was carried out using Smart PLS (Partial Least Square) software using the Structural Equation Modeling (SEM) approach. The research results show that implementing the human resource management strategy, namely the high-performance work system, significantly influences employee job satisfaction at the Labuhan Deli Class I Detention Center. Keywords: High-Performance Work System; Job Satisfaction; Labuhan Deli Class I Detention Center